(untitled) (Eurasian Research Bulletin, 2022)
This article analyzes the content of the formation of social activity on the basis of the formation of base competencies in students, the ability to overcome conflicts and problems that have arisen as a component of social activity, facilitating students to take a worthy place in the microsocium in the future, important components of social activity that are not always manifested.